Authority of Banking Supervision And Regulation By Bank Indonesia And Financial Services Authority (OJK) - Asep Hery; Surti Yustianti; Daniel Susilo (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2019)
This study analyzes the regulatory and supervisory authority of banks conducted by the Financial Services Authority set out in Law no. 21 of 2011 which was previously undertaken by Bank Indonesia in fact to apply the principles of prudence and good faith principles to banks in order to prevent the risk of banking crime. Banking supervision and regulation after the issuance of the OJK Law (Financial Services Authority), Bank Indonesia as the central bank only acts as a monetary policy regulator to maintain monetary stability. The problem in this research is about the concept of law of regulation and supervision of banking sector by OJK and how the legal relationship with Bank Indonesia. The type of research used is juridical normative, then the data used secondary data and primary data, the approach in this study using conceptual approach, and komporatif. Bank Indonesia's regulatory and supervisory duties transferred to OJK are only related to microprudential, and the banking arrangements by Bank Indonesia are still conducted by Bank Indonesia only macroprudential, while the regulation of banking by OJK is not fully independent.